Effect of Boron and Sowing Dates on the Nutrients Concentration and Uptake in Wheat (Triticum aestivum) - Islam, MS; Jahiruddin, J (The Agriculturists, 2010)
The effect of boron and different dates of sowing on some wheat cultivars was studied at BAU farm during winter season of 2006-07. There were two boron treatments (0 and 1 kg B ha-1), three wheat cultivars (Prodip, Shatabdi and Sourav) and four sowing dates (18 November, 28 November, 08 December and 18 December, 2006). The experiment was conducted in a split-split plot design in the three replications. The grain samples were analyzed for N, P, K and B, while the straw samples were analyzed for P, K and B contents and uptake. Both N and B concentrations of grain were significantly increased by boron application.